Symposium 2: Performing Blended Learning as a Product and a Service - O'Keeffe, Cormac; Parchoma, Gale (Proceedings of the International Conference on Networked Learning, 2014)
Blended and networked learning discourses tend to focus on relations among learners, tutor/professor/teachers, peers, and material learning resources. While in higher educational contexts there is logic to this discursive practice, the roles of non-educator and technological actants in blended learning networks are often neglected or relegated to marginal positions. Non-educators’ contributions to commercial assemblages of blended learning networks can be perceived as out-sider performances, in which values are more aligned to neo-liberal, managerial practices. The roles of technological actants across contexts remain under theorised. We trace interactions among sales and service staff, technological actors, and learners in a commercial blended learning assemblage and problematise a commodified performance of blended learning in relation to blended and networked learning theorised practices. Using Callon’s notion of socio-technical capacities and assemblages, we redeploy attributes of a blended-learning network where interactions among sales and service staff, learners, technological artefacts and actants are described. The roles sales and service staff and technological agents in a second language enterprise perform blended learning as an assemblage that binds companies, human personnel, and learners. Using this approach, informed by material-semiotics, we follow the sequence of transformations that are involved in the production, distribution, and consumption of blended learning. Non-educator and non-human actants in sales, service, and administrative roles actively work to strengthen blended learning assemblages, making them more - or less - durable over time, while having little or nothing to do with supporting cooperative or collaborative learning activities central to theorised blended and network learning practices. Yet these actants perform key roles in performing blended learning as a product and a service in commercial settings that connect theories of blended learning.